PENYULUHAN PERTOLONGAN PERTAMA BACK BLOW DENGAN PENGETAHUAN ORANG TUA DALAM PENANGANAN SUMBATAN JALAN NAFAS OLEH BENDA ASING PADA ANAK DI TAKENGON - Edriyani Simanjuntak; Johansen Hutajulu; Henny Syapitri (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Airway obstruction by a foreign body is an emergency that requires immediate treatment often occurs in children aged less than 3 years. This study aims to determine the relationship of knowledge with handling techniques airway obstruction by a foreign body which carried out the family in children less than 3 years in the village of Kute Lot Takengon. Type of research is descriptive research with cross sectional correlational. The population in this study is a family in the village of Kute Lot Takengon, with a sample of 40 families that mothers using total sampling and test (Spearman).The results showed a family of knowledge in the handling of airway obstruction by a foreign body in children less than 3 years old enough to be in a category by 60 % while handling technique family with airway obstruction by a foreign body in children less than 3 years the majority is not done by 75 %. The results showed a correlation value of 0,424 with p value < a ( 0.006 < 0.05 ) means that there is a significant relationship between knowledge and handling techniques airway obstruction by a foreign body which carried out the family in children less than 3 years in the village of Kute Lot Takengon.For nursing practice is expected to provide counseling and health education to the public about handling techniques airway obstruction by a foreign body in children aged less than 3 years so that people can have knowledge of experience in preventing and provide treatment airway obstruction by a foreign body in children.